FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN PERUSAHAAN - Desy Millenia; Linda Santioso (Jurnal Paradigma Akuntansi, 2026)
The objective of this study is to look into the effects of profitability, firm size, leverage, growth prospects, and liquidity on dividend policy in consumer non-cyclicals firms listed on the Indonesia Stock Exchange between 2019-2021. Purposive sampling was used to pick the sample, which yielded 29 firms that satisfied the criteria. SPSS (Statistical Product and Service Solution) version 25 is used in this study to do multiple regression analysis and data processing. Profitability has a negative and insignificant effect on dividend policy, firm size has a positive and insignificant effect on dividend policy, leverage has a negative and insignificant effect on dividend policy, growth prospects have a positive and insignificant effect on dividend policy, and liquidity has a positive and significant effect on dividend policy, according to the findings of this study. This research has the potential to be useful to investors and businesses in making decisions.